2014
DOI: 10.1073/pnas.1414770111
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal domain small phosphatase 1 and MAP kinase reciprocally control REST stability and neuronal differentiation

Abstract: The repressor element 1 (RE1) silencing transcription factor (REST) in stem cells represses hundreds of genes essential to neuronal function. During neurogenesis, REST is degraded in neural progenitors to promote subsequent elaboration of a mature neuronal phenotype. Prior studies indicate that part of the degradation mechanism involves phosphorylation of two sites in the C terminus of REST that require activity of beta-transducin repeat containing E3 ubiquitin protein ligase, βTrCP. We identify a proline-dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 46 publications
4
45
0
Order By: Relevance
“…CK1 phosphorylates REST at serine residues within its degron motifs, enabling the E3 ligase β-TrCP to recognize and bind REST (the substrate) through phospho-degron motifs [15•]. A recent study by Mandel and colleagues identified a proline-rich sequence upstream of the phospho-degron motifs which, when phosphorylated by ERK1/2, facilitates loss of REST at the end stage of neural differentiation [60]. …”
Section: Regulation Of Rest Abundance In Neuronsmentioning
confidence: 99%
“…CK1 phosphorylates REST at serine residues within its degron motifs, enabling the E3 ligase β-TrCP to recognize and bind REST (the substrate) through phospho-degron motifs [15•]. A recent study by Mandel and colleagues identified a proline-rich sequence upstream of the phospho-degron motifs which, when phosphorylated by ERK1/2, facilitates loss of REST at the end stage of neural differentiation [60]. …”
Section: Regulation Of Rest Abundance In Neuronsmentioning
confidence: 99%
“…An additional mode of action has been recently proposed for Scps role in gene silencing. REST degradation and association with REST-complex cofactors is regulated by phosphorylation at S861 and S864 [130]. Phosphorylation of these residues increases REST affinity to E3 ubiquitin ligase SCF β-TRCP and reduces it's affinity to CoREST [130], a protein that binds the C-terminus of REST and helps recruit additional silencing factors [131].…”
Section: Introductionmentioning
confidence: 99%
“…REST degradation and association with REST-complex cofactors is regulated by phosphorylation at S861 and S864 [130]. Phosphorylation of these residues increases REST affinity to E3 ubiquitin ligase SCF β-TRCP and reduces it's affinity to CoREST [130], a protein that binds the C-terminus of REST and helps recruit additional silencing factors [131]. Scps directly dephosphorylate REST at S861/S864 both in vitro and in vivo , and can abolish these negative effects on REST function [130].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations